The Haughty Soul of the Avenger: The Myth of Lucius Brutus in the Aeneid (6,817–823) - Rung, Ádám (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
In Book 6 of the Aeneid, Virgil constructs his own version of an epic Underworld and, innovatively, combines it with a panoply of future Roman heroes. This article focuses on the laconic introduction given to one of these heroes, Lucius Iunius Brutus, the founding father of the Roman Republic. More specifically, it examines the opening lines of a striking passage that, in an act of diction that has puzzled readers since antiquity, applies the adjective superbus to Brutus, rather than to his adversary, Tarquin the Proud, whose cognomen bears precisely this meaning. To interpret these lines, the article will attempt—using other literary versions of the work combined with comparative material from similar narratives—to reconstruct the traditional story of Brutus as it was known to Virgil and his contemporaries to determine, firstly, if this elucidates what such a retelling would have meant to the Augustan reader and, secondly, what its possible political and cultural implications would be if read with the traditional myth in mind.